Anthropology of Civilization: Personal Reflections on Anthropological Approach in the Study of Muslim Societies in Southeast Asia - Mitsuo Nakamura (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2020)
After pursuing a long academic career as an anthropologist, this article provides my (Mitsuo Nakamura’s) personal academic reflection of how my anthropological approach differs from Geertzian paradigm, why anthropology and Islamic studies should be bridged, and what implications of the conversation between Islamic studies, anthropology, and other social sciences are. By answering the above questions, this reflective article sheds a new light on the relationship between anthropology and Islam and Muslim studies in Southeast Asia, especially Indonesia. The anthropological studies of Muslims in Southeast Asia that have been heavily influenced by Clifford Geertz through his work, The Religion of Java (1960), are engaged critically in this article. If Geertz and his students pay a more attention to Little Tradition (local culture and practices) and avoid Great Tradition (e.g. religious concepts and teachings), my anthropological approach argues for the importance of incorporating Great Tradition, which is Islamic Studies in the case of Muslim studies in Southeast Asia, in the study of anthropology and vice versa.